Stan i kierunki rozwoju rolniczych grup producenckich w Polsce - Krzyżanowska, Krystyna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2003)
The study reviews both condition of producer groups and trends in their development in Poland over the period till the end of the 2002. Additionally, some factors either stimulating or restraining this process were presented. At present, there exist 413 producer groups formally registered, amongst them 22 ones recorded in registers of voivodship offices.